2012
DOI: 10.1371/journal.pone.0045308
|View full text |Cite
|
Sign up to set email alerts
|

Human Lung Cancer Cells Grown in an Ex Vivo 3D Lung Model Produce Matrix Metalloproteinases Not Produced in 2D Culture

Abstract: We compared the growth of human lung cancer cells in an ex vivo three-dimensional (3D) lung model and 2D culture to determine which better mimics lung cancer growth in patients. A549 cells were grown in an ex vivo 3D lung model and in 2D culture for 15 days. We measured the size and formation of tumor nodules and counted the cells after 15 days. We also stained the tissue/cells for Ki-67, and Caspase-3. We measured matrix metalloproteinase (MMP) levels in the conditioned media and in blood plasma from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 22 publications
4
50
1
4
Order By: Relevance
“…Much more expensive for large-scale studies and high throughput assays than traditional 2D culture 17 Some models produce spheroids that vary greatly in size, resulting in high variability within the same well/flask 17 3D models still lack vasculature which plays a vital role in tumor growth/ survival and drug delivery 74,75 the electrical behavior of the spheroid includes the effective extracellular resistance of the spheroid, R ext ; the effective intracellular resistance of the spheroid, R int ; the effective cell membrane capacitance of the spheroid, C mem ; the electrical behavior of the detection system, which includes the stray capacitance of the system, C s ; and the resistance of the culture medium, R med . 89 Kloss et al demonstrated that drug-induced apoptosis in spheroids displayed increased impedance magnitudes, resulting from an altered morphology of the outer cells, using the microcavity system.…”
mentioning
confidence: 99%
“…Much more expensive for large-scale studies and high throughput assays than traditional 2D culture 17 Some models produce spheroids that vary greatly in size, resulting in high variability within the same well/flask 17 3D models still lack vasculature which plays a vital role in tumor growth/ survival and drug delivery 74,75 the electrical behavior of the spheroid includes the effective extracellular resistance of the spheroid, R ext ; the effective intracellular resistance of the spheroid, R int ; the effective cell membrane capacitance of the spheroid, C mem ; the electrical behavior of the detection system, which includes the stray capacitance of the system, C s ; and the resistance of the culture medium, R med . 89 Kloss et al demonstrated that drug-induced apoptosis in spheroids displayed increased impedance magnitudes, resulting from an altered morphology of the outer cells, using the microcavity system.…”
mentioning
confidence: 99%
“…Previous studies have shown that 3D cultured cells produce more unique proteins than 2D cultured cells and also the common secreted proteins in 2DCM and 3DCM was found to be enriched in 3DCM (Mishra et al 2012;Tit-Oon et al 2014). Thus, an in-depth proteomic analysis of the secretome can reveal the identity and function of the unique proteins found in this study.…”
Section: Discussionmentioning
confidence: 50%
“…Tumor cells can in fact be grown successfully in a decellularized ECM of an organ as shown in Mishra et al [43]. This allows mimicking the in vivo environment and has been done successfully for an ex vivo 3D lung model where it was possible to grow perfusable lung nodules [43]. The simulations are limited to the avascular stage.…”
Section: Comparison Between Mts Growth In An Ecm Deposited By Tcs Inmentioning
confidence: 99%